Functional Properties of Factor V and Factor Va Encoded by the R2-gene - Hoekema, Lico; Castoldi, Elisabetta; Tans, Guido; Girelli, Domenico; Gemmati, Donato; Bernardi, Francesco; Rosing, Jan (Thrombosis and Haemostasis, 2001)
Carriership of the factor V (FV) gene marked by the R2-haplotype, a series of linked polymorphisms encoding several amino acid changes in FV, is associated with mild resistance to activated protein C (APC) and with an increased risk of thrombosis. We compared the functional properties of normal FV(a) and R2-FV(a) in model systems and in plasma. FV and R2-FV were equally well activated by thrombin and expressed identical cofactor activities in prothrombin activation. Rate constants of APC-catalyzed inactivation of FVa and R2-FVa were similar both with and without protein S. However, significant differences were observed between haemostatic parameters determined in plasma from homozygous carriers of the R2-gene (n = 5) and age-matched non-carriers (n = 19). Plasma from R2-carriers contained significantly lower FV levels and the ratio of the two FV isoforms (FV1 and FV2) was shifted in favor of FV1. The FV2/FV1 ratio was 1.4 (95% CI = 1.3-1.5) in homozygous carriers of R2 and 2.8 (95% CI = 2.5-3.1) in controls (p <0.00001). In an APC resistance test which quantifies the cofactor activity of FV in APC-catalyzed FVIII(a) inactivation, homozygous R2-carriers had significantly lower (p <0.00001) APC sensitivity ratios (APCsr = 1.54, 95% CI = 1.48-1.60) than controls (APCsr = 2.17, 95% CI = 2.05-2.28). This indicates that R2-FV has reduced cofactor activity in APC-catalyzed FVIII(a) inactivation. The changes of the relative amounts of FV1 and FV2 in carriers of the R2-gene will result in increased thrombin formation in the presence of APC and may provide a mechanistic explanation for the increased thrombotic risk associated with the R2-haplotype.
Keywords: Factor V isoforms; R2-haplotype; APC-resistance